2008
DOI: 10.1016/j.trb.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Existence of urban-scale macroscopic fundamental diagrams: Some experimental findings

Abstract: A field experiment in Yokohama (Japan) reveals that a macroscopic fundamental diagram (MFD) linking space-mean flow, density and speed exists on a large urban area. The experiment used a combination of fixed detectors and floating vehicle probes as sensors. It was observed that when the somewhat chaotic scatter-plots of speed vs. density from individual fixed detectors were aggregated the scatter nearly disappeared and points grouped neatly along a smoothly declining curve. This evidence suggests, but does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
647
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,224 publications
(667 citation statements)
references
References 4 publications
13
647
1
6
Order By: Relevance
“…Then, for steady state queuing systems P m i ðtÞ ¼ O m i ðtÞ Á L im (Little, 1961) and V m i ðtÞ ¼ def P m i ðtÞ=n m i ðtÞ. Geroliminis and Daganzo (2008) have shown that trip length of cars in downtown Yokohama was a time invariant variable. The average trip length of buses can be easily estimated as buses have fixed routes.…”
Section: Multimodal Travel Time Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, for steady state queuing systems P m i ðtÞ ¼ O m i ðtÞ Á L im (Little, 1961) and V m i ðtÞ ¼ def P m i ðtÞ=n m i ðtÞ. Geroliminis and Daganzo (2008) have shown that trip length of cars in downtown Yokohama was a time invariant variable. The average trip length of buses can be easily estimated as buses have fixed routes.…”
Section: Multimodal Travel Time Estimationmentioning
confidence: 99%
“…While various theories have been proposed to macroscopically model urban networks (Godfrey, 1969;Herman and Prigogine, 1979;Mahmassani et al, 1987;Daganzo, 2007), only until recently Geroliminis and Daganzo (2008) demonstrated the existence of a fundamental model (the macroscopic fundamental diagram -MFD) on congestion dynamics of single-mode system with empirical data. This reference showed that (i) an MFD is a plot between network space-mean flow and density, (ii) the MFD is a property of the network itself (infrastructure and control) and not very sensitive to demand, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, the concept of Network Fundamental Diagram, NFD, often called Macroscopic Fundamental Diagram (MFD), has been adopted as a basis for the derivation of tra c control strategies (e.g., Leclercq et al (2014)). The theory was rst proposed in Godfrey (1969) and further developed in Daganzo and Geroliminis (2008) and Helbing (2009) (its application to experimental data is analyzed in Mahmassani et al (1987); Geroliminis and Daganzo (2008); Ampountolas and Kouvelas (2015)). Geroliminis and Sun (2011) further investigated what the properties that a network should satisfy are, so that an MFD with low scatter exists, by again using data from a eld experiment in Yokohama (Japan).…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that if two tra c states from two di erent time intervals have the same spatial distribution of link density, then the two time intervals have the same average ow. As a result, the assumption that congestion is evenly distributed across the network made by Geroliminis and Daganzo (2008) is relaxed. Daganzo (2007) rst used the NFD to synthesize a controller that maximizes the network out ow, thus comprising a starting point for using the NFD theory for controlling tra c ow.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [5] contains experimental results concerning this interdependence, which were obtained using a combination of detectors in the network and a vehicle fl eet equipped with sensors.…”
Section: Introductionmentioning
confidence: 99%